Facile method for the synthesis of gold nanoparticles using an ion coater - Lee, Seung Han; Jung, Hyun Kyu; Kim, Tae Cheol; Kim, Chang Hee; Shin, Chang Hwan; Yoon, Tae-Sik; Hong, A-Ra; Jang, Ho Seong; Kim, Dong Hun (ELSEVIER SCIENCE BV, 2018)
Herein we report a metal nanoparticle synthesis method based on a physical vapor deposition process instead of the conventional wet process of chemical reactions in liquids. A narrow size distribution of synthesized gold nanoparticles was obtained using an ion coater on glycerin at low vapor pressure. The nanoparticle size could be modulated by controlling the sputtering conditions especially the discharge current. Due to the formation of gold nanoparticles, a surface plasmon resonance peak appeared at similar to 530 nm in the absorption spectrum. The surface plasmon resonance peak exhibited red-shift with increasing size of the gold nanoparticles. Our results provide a simple, environmental friendly method for the synthesis of metal nanoparticles by combine low-cost deposition apparatus and a liquid medium, which is free from toxic reagents. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: SURFACE-PLASMON RESONANCE; METAL NANOPARTICLES; NANOCRYSTALS; CATALYSIS; SHAPE; SIZE; DEPOSITION; OCTAHEDRA; BIOLOGY